"Make glorious mistakes!" Fostering growth and wellbeing in HE transition. Issue 1 (2nd January 2022) - Coyle, Stella; Gibbons-Jones, Hannah
ABSTRACT: This paper uses Keele's Legal Essentials module as a case study to evaluate how curriculum design can promote wellbeing in first-year law students, by supporting their transition to higher education and fostering a sense of belonging to the Law School community. Module design is grounded in recognition that the orientation process for new law students should emphasise the importance of wellbeing 1 and that wellbeing initiatives are most effective when integrated into the curriculum. 2 Legal Essentials aims to give new law students an early experience of a community grounded in collaboration and authentic critical engagement, where risk-taking is fostered and supported. Module delivery incorporates co-teaching and panel-style discussions, including more senior students and members of the wider legal world. Academics, students, and professionals thereby share their own experiences of learning, practice, and wellbeing, modelling a community where vulnerability is not a weakness and collaboration is encouraged.